2016
DOI: 10.7314/apjcp.2016.17.1.25
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Lymph Node Metastasis in Papillary Thyroid Cancers

Abstract: Lymph node metastasis (LNM) in papillary thyroid cancer (PTC) has been shown to be associated with increased risk of locoregional recurrence, poor prognosis and decreased survival, especially in older patients. Hence, there is a need for a reliable biomarker for the prediction of LNM in this cancer. MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene translation or degradation and play key roles in numerous cellular functions including cell-cycle regulation, differentiation, apoptosis, invasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 114 publications
1
17
0
Order By: Relevance
“…However, the occurrence and progression of TC were generally attributed to long-term interactions between environmental and genetic factors. Accumulating studies have re- ported that molecular mechanisms act an important role in human thyroid carcinogenesis and a large number of ncRNAs participate in the process [3,5,29,30]. Hence, it is of important significance to excavate abnormally expressed lncRNAs and their related signaling pathways, which will provide adequate theoretical basis to interpret the underlying mechanisms and to search effective therapeutic targets for TC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the occurrence and progression of TC were generally attributed to long-term interactions between environmental and genetic factors. Accumulating studies have re- ported that molecular mechanisms act an important role in human thyroid carcinogenesis and a large number of ncRNAs participate in the process [3,5,29,30]. Hence, it is of important significance to excavate abnormally expressed lncRNAs and their related signaling pathways, which will provide adequate theoretical basis to interpret the underlying mechanisms and to search effective therapeutic targets for TC.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid carcinoma (TC) is the most common malignancy of endocrine organs worldwide, with steadily increasing morbidity during the last 3 decades [1,2]. To date, numerous studies have suggested that complex biological processes involving the interaction of multiple genes might participate in the development of TC [3][4][5]. In addition to protein-coding genes, 6 types of long noncoding RNAs (lncRNAs) have recently been reported to be involved in human thyroid carcinogenesis, including MEG3 [6], PTCSC3 [7], BANCR [8], PVT1 [9], NONHSAT037832 [10], and LOC100507661 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that miRNAs are aberrantly expressed in almost all types of human cancer, including PTC (12), colorectal cancer (13), lung cancer (14), glioblastoma (15) MicroRNA-766 inhibits papillary thyroid cancer progression by directly targeting insulin receptor substrate 2 and regulating the PI3K/Akt pathway and bladder cancer (16). Increasing evidence has revealed that various miRNAs are differentially expressed in PTC, and their dysregulation has been implicated in the regulation of PTC occurrence and development (17)(18)(19). Furthermore, miRNAs may have tumor suppressive or oncogenic roles in the progression of PTC and are able to regulate various cancer-associated biological processes, including cell proliferation, cell cycle progression, apoptosis, invasion, metastasis and epithelial-mesenchymal transition (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, relying on molecular and genetic analysis, BRAF-only mutations have been found as the most frequent molecular alterations in LNM, whereas TERTp-only mutations are the most frequent alterations in distant metastasis (Melo et al, 2017). In addition, several miRNAs, such as miRNA-146b and miR-221/222, have also been shown to be potential biomarkers in predicting LNM (Mutalib et al, 2016). To date, studies focusing on the involvement of protein biomarkers in PTC with LNM are quite limited.…”
Section: Discussionmentioning
confidence: 99%